Comparative Effects of PCSK9 (Proprotein Convertase Subtilisin/Kexin Type 9) Inhibition and Statins on Postprandial Triglyceride-Rich Lipoprotein Metabolism. Issue 7 (July 2018) - Chan, Dick C.; Watts, Gerald F.; Somaratne, Ransi; Wasserman, Scott M.; Scott, Rob; Barrett, P. Hugh R.
Abstract : Objective—: Inhibition of PCSK9 (proprotein convertase subtilisin/kexin type 9) and statins are known to lower plasma LDL (low-density lipoprotein)-cholesterol concentrations. However, the comparative effects of these treatments on the postprandial metabolism of TRLs (triglyceride-rich lipoproteins) remain to be investigated. Approach and Results—: We performed a 2-by-2 factorial trial of the effects of 8 weeks of subcutaneous evolocumab (420 mg every 2 weeks) and atorvastatin (80 mg daily) on postprandial TRL metabolism in 80 healthy, normolipidemic men after ingestion of an oral fat load. We evaluated plasma total and incremental area under the curves for triglycerides, apo (apolipoprotein)B-48, and VLDL (very-LDL)-apoB-100. We also examined the kinetics of apoB-48 using intravenous D3-leucine administration, mass spectrometry, and multicompartmental modeling. Atorvastatin and evolocumab independently lowered postprandial VLDL-apoB-100 total area under the curves ( P <0.001). Atorvastatin, but not evolocumab, reduced fasting plasma apoB-48, apoC-III, and angiopoietin-like 3 concentrations ( P <0.01), as well as postprandial triglyceride and apoB-48 total area under the curves ( P <0.001) and the incremental area under the curves for plasma triglycerides, apoB-48, and VLDL-apoB-100 ( P <0.01). Atorvastatin also independently increased TRL apoB-48 fractional catabolic rate ( P <0.001) and reduced the number of apoB-48–containing particles secreted in response to the fat load ( P <0.01). In contrast, evolocumab did not significantly alter the kinetics of apoB-48. Conclusions—: In healthy, normolipidemic men, atorvastatin decreased fasting and postprandial apoB-48 concentration by accelerating the catabolism of apoB-48 particles and reducing apoB-48 particle secretion in response to a fat load. Inhibition of PCSK9 with evolocumab had no significant effect on apoB-48 metabolism. Abstract : Supplemental Digital Content is available in the text.